Multi-site calibration of the SWAT hydrological model and study of spatio-temporal variation of water balance components in the Narayani River Basin, central part of Nepal - Nirajan Devkota; Suraj Lamichhane; Pawan Kumar Bhattarai (H2Open Journal, 2024)
Science-policy interaction is vital for addressing hydro-climatic disasters in data-limited regions, with modeling and analysis as key components. The utilization of the soil and water assessment tool (SWAT) model facilitated an evaluation of water balance variations across time and space within Narayani Basin through multi-site calibration. The adjustment of all parameters via the SUFI-2 algorithm revealed that precipitation and temperature lapse rate (PLAPS and TLAPS) exhibit higher sensitivity in scenarios where observed stations fail to capture orographic effects. The calibrated model accurately replicated evapotranspiration, net water yield, and groundwater flow for each sub-basin, including average flow and flow duration curve at calibration points. Findings indicated that 22% of precipitation is lost to evaporation, while 75% contributes to basin runoff, showcasing significant spatial and temporal variability in water balance components. Notably, net water yield comprises 44% lateral flow, 38% surface flow, and 16% groundwater flow, with distinct spatial patterns favoring lateral flow in the Himalayas and groundwater flow in the plains due to topographical variations. These outcomes offer actionable insights for policymakers and water resource managers, enabling assessments of climate and land use impacts and facilitating the formulation of policies for sustainable water resource utilization. HIGHLIGHTS Variability of water balance components in rugged topography, including groundwater and surface water interactions.; The research output would be applicable for planning water resource development and policy formulation.; A hydrological model has been developed using a multi-site calibration and validation approach, which will be valuable for future studies, such as climate change impact assessments.;